2000
DOI: 10.1029/2000wr900059
|View full text |Cite
|
Sign up to set email alerts
|

A physicochemical model for colloid exchange between a stream and a sand streambed with bed forms

Abstract: Abstract. Fine sediment exchange between a stream and the surrounding subsurface influences downstream contaminant transport and stream ecology. Fundamental models for this exchange were developed on the basis of (1) the hydraulics of bed form-driven advective pore water flow and (2) subsurface colloid transport processes. First, a model was developed to predict the advective flow induced in a sand bed by stream flow over bedforms. The resulting "pumping" exchange rate was calculated based on the streamflow co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
238
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 156 publications
(248 citation statements)
references
References 30 publications
10
238
0
Order By: Relevance
“…This paper will present a new model for fine particle exchange with a sand bed covered by moving dunes and ripples, i.e., for the case where stream velocities are sufficiently high to produce bed-load sediment transport with downstream motion of dune-shaped bed forms. This extends the range of applicability of the models presented in our previous work [Packman et al, 2000a]. We also report the results of flume experiments with moving bed forms, and demonstrate that the model yields good predictions of exchange when the bed form celerity is sufficiently high.…”
supporting
confidence: 51%
See 4 more Smart Citations
“…This paper will present a new model for fine particle exchange with a sand bed covered by moving dunes and ripples, i.e., for the case where stream velocities are sufficiently high to produce bed-load sediment transport with downstream motion of dune-shaped bed forms. This extends the range of applicability of the models presented in our previous work [Packman et al, 2000a]. We also report the results of flume experiments with moving bed forms, and demonstrate that the model yields good predictions of exchange when the bed form celerity is sufficiently high.…”
supporting
confidence: 51%
“…Colloid filtration is the physicochemical process whereby suspended particles become attached to stationary sediment grains in a porous medium. In flume experiments we observed that particle settling and filtration in the bed caused suspended clay to behave very nonconservatively [ We also previously observed that pumping transport of colloids to the deep bed will often result in nearly all colloids becoming trapped [Packman et al, 2000a[Packman et al, , 2000b. Thus it will also be assumed that exchanged particles are completely removed from suspension when they penetrate below the zone of active bed sediment transport.…”
Section: Exchange Of Colloids With Stationary Bed Formsmentioning
confidence: 96%
See 3 more Smart Citations